Indonesian Millenials Online Shopping Behavior - Salim, Muhartini; Alfansi, Lizar; Darta, Effed; Anggarawati, Sularsih; Amin, Armelly (International Review of Management and Marketing, 2019)
The aims of this study were to investigate : 1. Perceived risk by consumers influencing on consumer online shopping intention. 2. Consumers trust influencing consumers' online shopping Intention. 3. The difference between hedonistic shopping motivation and utilitarian shopping motivation as moderation of the influence of perceived risk by consumers in online shopping intentions. Between hedonistic and utilitarian shopping motivation which variable is the stronger? 4. The difference between hedonistic shopping motivation and utilitarian shopping motivation as moderation of the influence of consumer trust in online purchase intentions. Between hedonistic and utilitarian shopping motivation which variable is the stronger? The data in this study is obtained from a questionnare distributed to 210 responden. The method used in sampling is Purposive Sampling addressed to the whole millennial generation in Indonesia who have had online shopping respondents. The method through the Partial Least Squares (PLS) program, SmartPLS2.0 and t test. The results showed that perceived risk of consumers has a negative effect on shopping intention, and consumer trust has a positive effect on shopping intention. Futher the hedonistic shopping motivation is the stronger variable than utilitarian shopping motivation. Keywords: Shopping Intention, Perceived Risk, Trust, Hedonistic shopping motivation, Utilitarian shopping motivation. JEL Classifications: M, M0, M31 DOI: https://doi.org/10.32479/irmm.7684